PENERAPAN METODE MATERNAL REFLEKTIF (MMR) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA DENGAN HAMBATAN PENDENGARAN - Tiana Putri; Murni Winarsih; Trisna Mulyeni (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
The purpose of this classroom action research was to improve the reading comprehension of students with hearing impairments through the application of Maternal Reflective Methods (MMR) in the learning activity. Based on the results of observations and initial tests on students with hearing impairment in grade 4 of school for students with disabilities, it is evident that students reading comprehension skills need to be improved further. The Maternal Reflective Method is utilized to improve reading comprehension for students with hearing impairments. The research participants consisted of a male and three females with hearing impairment students. The research was held in two cycles. Each cycle consists of 4 stages: planning, implementation, observation, and reflection. The data were obtained through classroom observation, reading comprehension tests, and supplementary documents. The results showed that the utilization of the Maternal Reflective Method in learning activity could significantly improve reading comprehension for students with hearing impairments.